Deciphering the molecular basis of lipoprotein recognition and transport by LolCDE - Wen Qiao; Chongrong Shen; Yujiao Chen; Shenghai Chang; Xin Wang; Lili Yang; Jie Pang; Qinghua Luo; Zhibo Zhang; Yingxin Xiang; Chao Zhao; Guangwen Lu; et al. (Signal Transduction and Targeted Therapy)
Abstract Outer membrane (OM) lipoproteins serve vital roles in Gram-negative bacteria, contributing to their pathogenicity and drug resistance. For these lipoproteins to function, they must be transported from the inner membrane (IM), where they are assembled, to the OM by the ABC transporter LolCDE. We have previously captured structural snapshots of LolCDE in multiple states, revealing its dynamic conformational changes. However, the exact mechanism by which LolCDE recognizes and transfers lipoprotein between domains remains unclear. Here, we characterized the E. coli LolCDE complex bound with endogenous lipoprotein or ATP to explore the molecular features governing its substrate binding and transport functions. We found that the N-terminal unstructured linker of lipoprotein is critical for efficient binding by LolCDE; it must be sufficiently long to keep the lipoprotein’s main body outside the complex while allowing the triacyl chains to bind within the central cavity. Mutagenic assays identified key residues that mediate allosteric communication between the cytoplasmic and transmembrane domains and in the periplasmic domain to form a lipoprotein transport pathway at the LolC–LolE interface. This study provides insights into the OM lipoprotein relocation process mediated by LolCDE, with significant implications for antimicrobial drug development.